Farm water quality monitoring system via IoT technology / Akmal Hafiz Samsir - Samsir, Akmal Hafiz (2023)
This thesis represents the invention on farming system, called as Farm Water Quality Monitoring System via IoT Technology to help people who are facing food poisoning from bad produce cause by bad source of water and solve them by create a monitoring system that can be access anywhere with the current technologies of mobile phones. The purpose of this research is to simulate the circuit of systems in Farm Water Quality Monitoring System via IoT Technology using Proteus 8 Professional software, to design the prototype of Farm Water Quality Monitoring System via IoT Technology and test the prototype of Farm Water Quality Monitoring System via IoT Technology. This project consists of three parameters which are temperature sensor, pH sensor and turbidity sensor. An I2C LCD display was used to display the data of the current parameters of the water and an addition of LED and Buzzer to notify the current state of the water. Lastly, a NodeMCU ESP8266 are used to send data from the project through Wi-Fi network. Hence, Farm Water Quality Monitoring System via IoT Technology project is in line with the purpose of Final Year Project which is to learn about how to work independently and invent something that can solve problems that occurred in humans’ daily life.